Intellectual Capital Disclosures in IPO Prospectuses of Indian Companies - Bhatia, Meena; Agarwal, Bhawna (International Journal of Social Sciences and Management, 2015)
The study is based on companies that went through IPO on the Bombay Stock Exchange (BSE) and/or National Stock Exchange in the period 2011-2012. The paper applied a disclosure index comprising of 78 items to quantify the amount of information regarding intellectual capital included in the IPO prospectuses of Indian companies. The sum of disclosed score is divided by 78 to arrive at the index. For disclosure index content analysis is used. Multiple regression model and Correlation is used to examine the significance and association between disclosure index with independent variables. The main objective of this paper is to study the extent of intellectual capital disclosures in Initial Public offering (IPO) prospectus of Indian companies and also to examine the factors that influence the intellectual capital disclosure. The regression results reveal that of all the independent variables studied i.e. Board size Board independence Size Age Leverage Managerial ownership and Industry differences; Intellectual capital disclosure is influenced by industry differences. India is considered as knowledge economy and has highest contribution in gross domestic product from services sector wherein intellectual capital plays the most important role. As regards intellectual capital the studies have been insufficient. To our knowledge this is the first research on intellectual capital disclosures in IPO prospectuses of Indian companies. DOI: http://dx.doi.org/10.3126/ijssm.v2i1.11685 Int. J. Soc. Sci. Manage. Vol-2, issue-1: 40-51